High-moisture, acid-treated grain for finishing swine - Allee, G.L.; Deyoe, C.W.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The feeding value of high-moisture milo treated with organic acids for finishing swine was studied in two trials involving 56 pigs. There were no significant differences in daily gain, feed intake, feed efficiency, or carcass measurements between pigs fed the dry grain and those fed the high-moisture grain treated with organic acids. Preserving milo with organic acids apparently has no detrimental effect on performance or carcass merit when fed to finishing pigs.
Swine Industry Day 1972 is known as Swine Day 1972
Keywords: Swine; Acid-treated grain; Finishing swine; Milo